Stress profiling of the hematological, biochemical and acute phase protein responses to caprine trypanosoma evansi infection - Wong, Meng Tack (2011)
Trypanosoma evansi is a cosmopolitan haemoflagellate and is the most widely distributed of the pathogenic animal trypanosomes affecting domesticated livestock and wild animals. Goats appear to be resistant to the disease but various reports have indicated that they may serve as potential reservoirs of the infection. The dynamics of the disease and the interaction between the caprine host and parasite remains unclear. The present study was undertaken to ascertain the response of the Hypothalymic-pituitary-adrenal (HPA) axis to T. evansi infection in goats with reference to cortisol levels; to determine the alterations in putative haematological and serum biochemical stress markers, as well as to investigate the acute phase response of haptoglobin and serum amyloid-A. The dynamics of T. evansi infection was studied in 10 female Boer goats 8-10 months of age. The goats were divided into two equal groups (A and B), kept in adjacent pens in a fly-proof house and maintained in a similar manner throughout the experiment. Animals of group A were infected with 1 x 104 T. evansi trypomastigotes intravenously while animals in group B were injected with Phosphate Buffered Saline with 10% Glucose (PBSG) at the start of the experiment. The animals were bled every alternate day from day 0 to day 62 post infection (pi). Infected animals were treated with diminazene diaceturate on day 62 pi. Blood was collected every six days for a month after the treatment. Whole blood was examined for parasitaemia as well as levels of circulating leukocytes, neutrophils and lymphocytes. Plasma was analysed for cortisol, albumin, globulin, creatinine, lactate, haptoglobin (Hp) and serum amyloid-A (SAA). Three peaks of parasitaemia were apparent in the infected animals; the first and highest peak occurred on day 6 pi followed by the second peak on day 14 pi and a third minor peak on day 28 pi. The infected group showed three main peaks of cortisol increment on days 4, 20 and 28 pi, correlating with the peaks of parasitaemia. Plasma creatinine did not differ significantly in both experimental groups with the exception of one spike in the infected goats on day 12 pi which corresponded to the first major parasitaemia peak. Elevations in plasma lactate were apparent from day 16-24 pi, but dropped to basal values thereafter. The infected animals also showed a significant and progressive decrease in plasma albumin and a corresponding increase in plasma globulin throughout the course of the infection. The haemogram in the infected goats revealed leukopaenia and lymphopaenia early in the infection with marked chronic neutropaenia. The mean plasma levels of Hp and SAA were significantly elevated in the infected group, corresponding to the high levels of circulating parasites. Collectively, the changes observed in plasma cortisol, serum biochemistry, haematology and acute phase proteins indicate that T. evansi has the potential to elicit a measurable stress response in goats, with each metabolite having a unique pattern of expression. These ruminants are also potential chronic carriers of the parasite, making them efficient reservoirs of the pathogen and an important contributor to the epidemiology of livestock trypanosomiasis in the country.